Relationship Between Gender, Age, and BMI with Body Flexibility at MAN 2, Sleman, Yogyakarta - Utami, Jacoba Nugrahaningtyas Wahjuning; Nurtyas, Maratusholikhah (MultiTech Publisher, 2024)
Flexibility is important for general health and fitness, athletic performance, injury prevention and rehabilitation. Sedentary behavior in students causes a decrease in physical fitness levels which affects flexibility. There is little research on flexibility in relation to BMI. The purpose of this study was to determine the relationship between gender, age, BMI with body flexibility. The method used was descriptive analytic of secondary data with a cross section approach and analyzed with univariate using frequency distribution and bivariate analysis using chi square. The results of the study were 81 respondents. Women are more than male respondents, namely 71.6% or as many as 58 respondents. While the most age is teenage age (<25 years) of 67.9% or as many as 55% and most respondents have normal BMI, namely 61.7% or as many as 50 respondents. While the cross tabulation of age with flexibility shows a P-value> 0.05, namely 0.73, while the cross tabulation of gender and body flexibility shows a p-value> 0.05, namely 0.296, and for cross tabulation of the relationship between BMI and body flexibility is p-value> 0.05, namely 0.458. Conclusion There is no relationship between age, gender, BMI and flexibility